Quelles politiques pour des transports sans rupture? Aspects institutionnels et réglementaires de la coordination intermodale - Stephen Perkins (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
– This paper briefly discusses inter-modal coordination of transport services from a perspective of what could be called "diversity-based mobility policy". It examines the framework conditions for inter-modal competition and coordination under an approach to transport policy making that reflects the broad variety of mobility needs and aspirations in market economies and reflects the social opportunity costs of alternative ways of addressing the demand for mobility. The paper discusses integrated land-use planning and transport policy making, the importance of institutional frameworks for integrated transport planning and the fiscal framework for inter-modal competition, including in relation to external costs. Competition for resources between freight and passenger services is considered as well as truly inter-modal issues. The paper was prepared for the National Transport Development Policy Committee of the Government of India following a Workshop in Delhi in February 2012, supported by the World Bank, Ausaid and the International Transport Forum. At the request of the Committee the paper focuses mainly on transport policy making in Europe but it also draws on experience in Japan, Russia and North America.
Keywords: 330